Pengembangan Buku Cerita Bergambar “Petualangan Pancasila” Sebagai Media Pendidikan Karakter Pada Siswa Sekolah Dasar - Naqiyyah, Deva Khofifah Jauharotun; Wibowo, Bangun Yoga; Handoyo, Alfiandy Warih (Lembaga Riset dan Inovasi Almatani, 2025)
ABSTRACT This research aims to develop picture story books as a character education learning medium for elementary school students. The research method used is Research and Development (RnD) with the ADDIE development model approach. This model includes five stages, namely analysis, design, development, implementation and evaluation. The research participants consisted of 57 phase B students at SDIT El-Syarief, with a limited trial involving 36 students selected using the simple random sampling method. Data was collected via questionnaire as a research instrument. The results of the product feasibility test showed that the media feasibility test score reached 75%, the language feasibility test was 81%, the material feasibility test was 86%, and the practitioner feasibility test was 83%, resulting in an overall average of 83%, which was categorized as